Bifocal stance theory, the transmission metaphor, and institutional reality. (10th November 2022) - Packer, Martin J.; Cole, Michael
Abstract: Biologists have replaced the metaphor of "genetic transmission" with a detailed account of the molecular mechanisms underlying the phenomenon which Darwin referred to as "like produces like." Cultural evolution theorists, in contrast, continue to appeal to "imitation" or "copying." The notion of ritual and instrumental stances does not resolve this issue, and ignores the institutions in which people live.